2009
DOI: 10.1063/1.3187914
|View full text |Cite
|
Sign up to set email alerts
|

The determination of the bulk residual doping in indium nitride films using photoluminescence

Abstract: We extend to any temperature, the sophisticated calculation of the evolution of the 2 K photoluminescence energy of InN proposed by Arnaudov et al. [Phys. Rev. B 69, 115216 (2004)], in view of determining the residual doping of thin films. From the detailed line shape modeling, we extract the full width at half maximum of the photoluminescence line which, in the first order, varies like n0.51 at low temperature. This allows us to propose a handy tool for rapid residual doping evaluation. Last, temperature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…In the case of InN, free electron concentration increases the emission linewidth following a power law, as shown by a recent study. 45 According to this work, an inhomogeneous broadening of ϳ10 meV and a moderate electron density ͑between 1.0ϫ 10 17 and 5.0ϫ 10 17 cm −3 ͒ would account for the measured FWHM of the current epilayer.…”
Section: Discussionmentioning
confidence: 71%
“…In the case of InN, free electron concentration increases the emission linewidth following a power law, as shown by a recent study. 45 According to this work, an inhomogeneous broadening of ϳ10 meV and a moderate electron density ͑between 1.0ϫ 10 17 and 5.0ϫ 10 17 cm −3 ͒ would account for the measured FWHM of the current epilayer.…”
Section: Discussionmentioning
confidence: 71%
“…This routine leads, after the line shape fitting has been successfully achieved, to the values of the bulk residual doping and to the value of the band gap at 2 K. We note that the low temperature broadening of the PL is correlated to the square root power of the doping as shown in Ref. 13. It is also worthwhile telling here that this routine also correlates the decrease of the PL intensity with the residual doping, a well‐known doped semiconductors textbook effect not recalled in Ref.…”
Section: Resultsmentioning
confidence: 86%
“…To get rid of the influence of spatially extended topological defects that may alter electron drift and correlate the measurement of mobility to sample dimensions, we have alternatively determined the bulk doping of our layers via a line shape fitting of the PL. We used a home‐made program 13 based on the work of Arnaudov et al 14. This routine leads, after the line shape fitting has been successfully achieved, to the values of the bulk residual doping and to the value of the band gap at 2 K. We note that the low temperature broadening of the PL is correlated to the square root power of the doping as shown in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…8,[19][20][21][22][23][24][25][26][27][28][29][30] For example, in general, the currently reported nominally undoped InN is n-type degenerate, with the residual electron densities in the range of ∼ 1 × 10 18 cm −3 , or higher. 8,11,25,[31][32][33][34] Moreover, it has been generally observed that there exists a very high electron concentration (∼ 1 × 10 13−14 cm −2 ) at both the polar and nonpolar grown surfaces of InN films, 19,35 and the Fermi-level (E F ) is pinned deep into the conduction band at the surfaces; 19,20,29,30 similar electron accumulation profile has also been measured at the lateral nonpolar grown surfaces of [0001]-oriented wurtzite InN nanowires. 8,11,21,22,25,36 In this regard, significant efforts have been devoted to understanding the fundamental surface charge properties of InN.…”
mentioning
confidence: 68%